P255 Mirikizumab modulates genes associated with the symptom of bowel urgency. (21st January 2022) - Krishnan, G; Steere, B; Higgs, R; Wang, Y C; Harris, C J; Milch, C; Escobar, R; Reinisch, W; Dubinsky, M
Abstract: Background: Bowel urgency (BU) is one of the most common and distressing symptoms experienced by patients (pts) with ulcerative colitis (UC). Mirikizumab (miri), a p19-directed IL-23 antibody, demonstrated efficacy and an acceptable safety profile in a phase 2 randomized clinical trial in pts with moderately to severely active UC. We have previously shown that miri significantly downregulates transcripts associated with disease activity defined by modified Mayo score and Robart's Histopathology Index, and upregulates genes expressing transporter proteins associated with healthy mucosa in pts with UC. Here we investigate associations between colon tissue transcripts and patient-reported BU at Baseline (BL) and Week (W)12. We assess the effect of miri induction treatment on genes associated with BU. Methods: Pts were randomized 1:1:1:1 to receive intravenous placebo (N=63), miri 50mg (N=63) or 200mg (N=62) with possibility of exposure-based dose increases, or fixed miri 600mg (N=61) every 4 weeks for 12 weeks. Patient colonic biopsies were collected at BL and W12 (placebo N=58, miri 50mg N=52, 200mg N=51, 600mg N=54). Gene expression was measured using an Affymetrix HTA2.0 microarray workflow. Differential gene expression was determined by paired T-test comparing expression values at W12 and BL. BU was reported daily by pts as yes/no. Proportion of days of BU at BL and at W12 was calculated for the 3 days prior to visit on a 4-point ordinal scale (0: absence of urgency on all 3 days; 3: presence of urgency all 3 days). BL and W12 gene expression and BU values were pooled and associations identified based on non-parametric Kendall's tau. Pathway analysis of correlated genes were performed using over-representation analysis on Hallmark and Reactome gene sets from MSigDB. p values of enrichment were determined by hypergeometric distribution test and adjusted for multi-testing with Benjamini-Hochberg (BH) procedure. Results: A total of 249 pts reported BU scores at BL and W12. The presence of BU was associated with 320 genes (|tau|> 0.225 and qval <0.001). Pathway analysis identified pathways significantly associated with BU (Table). Among the 320 correlated transcripts, 296 were positively correlated (higher gene expression) and 24 were negatively correlated (lower gene expression) with the frequency of BU. Treatment with miri (200mg) resulted in a statistically significant decrease in the 296 transcripts positively correlated with BU, and an increase in the 24 transcripts negatively correlated with BU. Conclusion: This is the first study to identify colon-based transcripts pertinent to mucosal inflammation and healing that correlate with bowel urgency and that are consistently modulated by miri.